Comprehensive Evaluation of Ovarian Growths in Young Women - Mukta Agarwal; Smita Singh; Sudwita Sinha (Gynecology and Minimally Invasive Therapy)
Objectives: Adolescents represent a significant demographic in hospital outpatient visits, and it is important to give them special consideration and conduct a thorough examination for any adnexal pathology. The research aimed to study adnexal masses in adolescent females aged 10–19 years, including their clinical, biochemical, and radiological evaluations. The goal was to develop a treatment plan and analyze its relationship with histopathological findings. Materials and Methods: The study was carried out at a single center and included 124 participants in a descriptive research design. Results: During the study, 6.2% of adolescents had adnexal masses, with abdominal discomfort being the most common symptom (66.12%). Ultrasound scans showed cystic, solid, or complex masses in 41.6%, 23.4%, and 35% of cases, respectively. In 53.4% of the patients, tumors exceeding 10 cm in size were identified, while 66.67% exhibited elevated levels of tumor markers. Surgical procedures were necessary for 48.5% of adolescents, with laparoscopic cystectomy being carried out in 48.34% and staging laparotomy in 46.66%. Conclusion: Small asymptomatic cysts need to be monitored, but larger complex or solid tumors must all be thoroughly examined to rule out malignancy. Early diagnosis and preservation of the ovary should be the aim of treatment. Although guidelines exist for the treatment of adnexal masses in adults, there is limited information available in the literature regarding adolescents. Therefore, it is crucial to establish an appropriate surgical plan that preserves fertility in this vulnerable age group.